A fully reconfigurable series-parallel photovoltaic module for higher energy yields in urban environments - Calcabrini, Andres; Muttillo, Mirco; Weegink, Raoul; Manganiello, Patrizio; Zeman, Miro; Isabella, Olindo (Renewable energy, 2021)
Photovoltaic modules in the urban environment are very often exposed to uneven illumination conditions. The electrical interconnection between solar cells in a photovoltaic module limits the power that a solar module can generate under partial shading conditions. In this article, we introduce a PV module that is able to dynamically reconfigure the interconnection between its solar cells to minimise conduction and mismatch losses according to the irradiance distribution on its surface. Using an accurate simulation framework, it is determined that a reconfigurable PV module can generate over 12% more energy than a standard PV module with fixed topology and six bypass diodes, and as much energy as a fixed series-parallel module with six parallel strings, but at significantly lower currents. Simulation results are validated experimentally using a photovoltaic module with six reconfigurable blocks of cells controlled by a switching matrix on a high-performance solar flash simulator. •A fully reconfigurable series-parallel photovoltaic module is proposed.•The DC yield of the proposed module is compared to fixed shade-tolerant topologies.•Under partial shading, reconfigurable PV modules can boost energy yield over 12%.•Full-scale prototypes of the module and the switching matrix were built.•Experimental validation shows an excellent match with simulation results.